2016
DOI: 10.1002/ceat.201600074
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Hydrodynamic Bubble‐Liquid Turbulent Flows in Bubble‐Column Reactors

Abstract: Bubble dispersion characteristics play an important role in heat and mass transfer of bubble-liquid two-phase turbulent flows in bubble-column reactors. In order to quantitatively describe the influence of operation conditions and sparger design on two-phase turbulent hydrodynamics in terms of a computational fluid dynamics approach, a second-order moment bubble-liquid twophase turbulent model was developed to predict the effects of superficial gas velocity, liquid and gas density, liquid dynamic viscosity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Second, the small‐orifice sparger provided higher gas holdup than the large‐orifice one . This corresponded to the different diameters of bubbles produced by the orifices : small bubbles rose to the liquid surface more slowly than large bubbles and eventually stayed longer in the column.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the small‐orifice sparger provided higher gas holdup than the large‐orifice one . This corresponded to the different diameters of bubbles produced by the orifices : small bubbles rose to the liquid surface more slowly than large bubbles and eventually stayed longer in the column.…”
Section: Resultsmentioning
confidence: 99%
“…It is due to the size of bubbles generated by those air diffusers. H-1.2 diffuse has the largest orifice size, while F-sand has the smallest one, which resulted in the smallest bubble size, 3.14-4.90 mm, as discussed by previous studies [4,27]. Similar trends were noted in ALR for small orifice diffusers, F-sand, C-sand, and H-0.3, higher Vg resulted in larger bubbles, 3.27-6.27 mm (see Figure 3b).…”
Section: Bubble Diameter (D 32 ) and Rising Velocity (U B )mentioning
confidence: 51%
“…Figure 3 illustrated the bubble size as Sauter's mean value at different investigated diffusers and gas velocity (Vg) in both BCR and ALR. In BCR, it can be observed that the air bubbles distribute between 3.14 and 11.28 mm, while larger bubbles were obtained in the higher gas flow, regardless of diffuser classes due to the bubble coalesce and high-pressure promotion at a higher flow (see Figure 3a) [24,27]. In general observation, smaller bubbles were observed from the use of a smaller orifice size diffuser (see Table 1) through the bubble formation phenomena.…”
Section: Bubble Diameter (D 32 ) and Rising Velocity (U B )mentioning
confidence: 82%
“…Bubble columns are widely employed in the industry to conduct gas‐liquid and gas‐liquid‐solid catalytic reactions in view of their merits compared to stirred‐tank reactors which suffer from problems such as high power consumption per unit volume, shaft sealing at high pressures, shaft eccentric rotation in tall reactors, and high shear rates which cause damage to the shear‐sensitive cultures involved in biochemical reactions 1–3. Bubble columns exhibit excellent mass and heat transfer characteristics, besides their high mixing efficiencies, simple design (no moving parts), and uniform temperature distribution 4–7. Despite the above favorable attributes of bubble‐column reactors, attempts have been going on to improve their performance furthermore by: (i) improving their productivity via increasing the rate of slow diffusion‐controlled liquid‐solid reaction step involved in gas‐liquid‐solid reactions; (ii) raising the rate of heat removal in case of highly exothermic reactions to avoid the adverse effects of high temperatures.…”
Section: Introductionmentioning
confidence: 99%